Linear precoding for interference suppression in multi-cell multi-user TDD MIMO downlink - Zu-jun LIU; Jie-ling WANG; De-chun SUN; Ke-chu YI (Tongxin xuebao)
To suppress multi-user interference (MUI) and inter-cell interference (ICI) existing in multi-cell multi-user TDD MIMO downlink,an interference suppression algorithm through designing precoder was proposed.Firstly,a precoding matrix was designed for MUI suppression,with the help of the QR decomposition of generalized MMSE channel inversion.And then the second precoding matrix was designed to suppress ICI and residual MUI,using a signal leakage criterion.The proposed algorithm could utilize TDD MIMO channel reciprocity,and thus did not require users' feedback information.The algorithm had been simulated in a multi-user TDD MIMO system composed of urban micro-cells.Simulation results show that,the proposed algorithm can effectively improve system capacity and user's average SINR.